Viscoelastic properties and pasting characteristics of fermented maize: influence of the addition of malted cereals - Ohene Afoakwa, E.; Adjonu, R.; Asomaning, J. (My University, 2010)
Investigations were conducted on the viscoelastic properties and pasting characteristics of fermented maize with malted cereals and their suitability for infant feeding. A 3 x 3 x 2 factorial experimental design with malting time, cereal malt concentration and cereal type was used. Maize, millet, and sorghum malts were added to fermented maize to reducing its bulk density. Samples were analysed for their viscoelastic properties and pasting characteristics using Brabender Viscoamylograph. Sorghum malt in comparison to millet and maize malts was not effective in terms of lowering the hot and cold paste viscosities of the fermented maize. Maize and millet malts liquefied the dough considerably during both the hot and cold paste viscosities. The effect of 4-day malted millet was most pronounced whilst the highest activity of maize malt was observed with the 3-day malted flours. The addition of maize and millet malts to fermented maize were most effective in lowering the viscoelastic properties of the resulting porridges.
Keywords: Cereals; fermentation; maize; malting; pasting characteristics; viscoelastic properties